Pengembangan UMKM Dalam Pemanfaatan Sumber Daya Alam Untuk Mendukung Perekonomian Keluarga - M. Soffan Rizqi; Bayu Ananda; Nurfaizah Nurfaizah; Deti Nurkhayati; Sitamala Rum Azizah; Indun Hafifah Indun; Umi Qonaatul Fauziah; M.; Samsul Huda; Dina; Abror Mutohar (Jurnal Pengabdian Masyarakat Madani, 2022)
MSME development in the use of natural resources to support the family economy. The existing problem is the lack of understanding and knowledge of MSME actors related to agricultural product innovation so that sales of agricultural products are still at standard prices. The purpose of this community service is to help change the mindset of the community in selling agricultural products so that they can increase the selling price so that they can support the family economy and reduce poverty. Using a participatory approach by involving the community in the process. The results of this service activity are in the form of providing counseling and a forum for product innovation results through competitions as a means of developing MSMEs. Then proceed with giving directions regarding product packaging and product marketing. Product innovations produced by MSME actors should be maintained and can be followed up so that they can be effective in supporting the development of MSMEs and can increase the selling price of products and can support the family economy